Sistem Manajemen Persediaan UD Logam Jaya Klaten - Joko Pitoyo; Wisnu Wendanto (Sekolah Tinggi Manajemen Informatika dan Komputer AUB - Indonesia, 2017)
Lack of supervision or management of goods in warehouses may cause the company's operations to be disrupted. UD's inventory management Metals have not been considered and well managed. This study discusses the inventory management information system to be implemented on UD Logam Jaya Klaten is a business that produces engine spare parts. With the inventory management is expected to be able to help maintain the availability of goods that allow the occurrence of goods run out, excess goods, loss of goods, or damage to goods. The research method used in doing research is waterfall method with ABC analysis and built with Visual Basic .Net programming language and using MySql database. The results achieved in the form of an application used to manage inventory at UD Logam Jaya Klaten. To overcome the problems regarding the company's operations caused by the lack of control of inventory in the warehouse then made inventory management information system that is able to overcome the problems of inventory of goods in UD Logam Jaya.Keywords: Information System, Inventory Management, UD Logam Jaya Klaten